Elements and types of advertising copywriting on instagram @batiksemarang16 - Setyowati, Bernadeta Lenny; Aydawati, Emilia Ninik (Interaksi: Jurnal Ilmu Komunikasi, 2025)
The Internet has helped marketers to reach larger markets and potential consumers at any time or place. The change in advertising activities and the advent of social media has moved marketers from conventional to social media because advertising costs are far cheaper and measurable. Marketing of batik products use Instagram to promote their products. This study is focused on the elements of copywriting and the types of copywriting applied to the social media of Instagram @batiksemarang16 as a marketing communication to their audiences. This study uses qualitative approaches and descriptive methods. The data collection techniques used are observation, a documentary of content containing elements of copywriting, copywriting from Instagram @batiksemarang16, and archive studies. Hopefully, the results of this study will become a reference to copywriting in the process of advertising on social media. The content of the @batiksemarang16 account uses the suggested elements of copywriting, such as headlines, sub-headlines and body copy, but instead of using slogans and taglines. This research found that combining copywriting elements makes content more creative and adds value to that copywriting. There were ten types of copywriting that were found on @batiksemarangang16.